Evaluation of Antioxidant Activity and Inhibition of Tyrosinase Activity of Raphanus sativus var. caudatus Alef Extract - YONGPRADOEM, Panadda; WEERAPREEYAKUL, Natthida (Walailak Journal of Science and Technology (WJST), 2020)
This study was aimed to determine antioxidant and tyrosinase inhibition effects of the pod of Raphanus sativus L. var. caudatus Alef extract. The compounds consisted in the extracts were identified by HPLC from standard peak comparison. Pod was extracted by using 2 different solvents-dichloromethane (DCM) and water. The antioxidant activity was evaluated based on free radical scavenging (DPPH) activity and ferric reducing ability (FRAP) assay. The lightening effect was determined from the inhibition of mushroom tyrosinase in vitro. The results showed that DCM extract contained sulforaphene, protocatechuic acid, p-hydroxybenzoic acid, caffeic acid, and ferulic acid. The aqueous extract contained sulforaphene, protocatechuic acid, p-hydroxybenzoic acid, caffeic acid, vanillic acid, and p-coumaric acid. The DPPH· scavenging effect expressed as the IC50 values for DCM and aqueous extracts were 883.38 ± 22.9 and 1,160.49 ± 22.30 µg/mL, respectively. The reducing power of aqueous extract (218.27 ± 0.010 µM FeSO4 equivalent) was greater than DCM extract (166.34 ± 0.018 µM FeSO4 equivalent) at the same concentration (2,000 µg/mL). However, both extracts showed lesser antioxidant activity than gallic acid, a positive control. DCM extract showed higher tyrosinase inhibitory effect than aqueous extract but lesser than kojic acid, a positive control. Both extracts at 2,000 µg/mL concentration exerted 42 and 19 % tyrosinase inhibition, respectively. In conclusion, the extraction solvent yielded different chemical constituents and thus the activities. The DCM extract exerted greater antioxidant activity and tyrosinase inhibition activity than the aqueous extract. The extract fractionation is required to get higher yields of bioactive compounds prior to further study and for cosmetics product development.